Orthodontic treatment stability and periodontal condition with circumferential supracrestal fiberotomy: a systematic review - Castaño-Duque, Sandra Patricia; Mora-Díaz, Ingrid Isabel; Losada-Amaya, Sergio Iván; Álvarez-Gómez, Lina María; Rengifo-Mosquera, Lina Marcela; Zerpa-Romandini, Ángela; Wasserman-Milhem, Isaac (Revista Facultad de Odontología Universidad de Antioquia, 2019)
Introduction: stability is one of the main goals of orthodontic treatment, and circumferential supracrestal fiberotomy is an alternative to prevent relapse in cases of tooth rotation, crowding and inclined teeth. However, there are no studies demonstrating the effectiveness of this treatment and its effects on the periodontal condition. The aim of this systematic review (SR) was to evaluate the effectiveness of circumferential supracrestal fiberotomy (CSF) as an adjuvant in the stability of orthodontic treatment during retention and its effects on the periodontal condition once it has been performed. Methods: the search for topic-related studies was conducted on the PubMed and EMBASE databases until October 2018. The studies were considered eligible if they covered the use of CSF during the retention period and reported the periodontal condition in a follow-up period longer than or equal to 1 year. For bias-risk assessment in the chosen studies, the Newcastle-Ottawa Scale was applied to observational studies, and the Cochrane Collaboration tool for Randomized Clinical Trials (RCTs) and Controlled Clinical Trials (CCTs). Results: the search strategy yielded 85 potential eligible articles, of which 5 were included in the SR. Four of the five studies reported a lower irregularity rate in patients who had CSF when compared to a control group. No changes in plaque index, gingival index, insertion levels, probe depth and keratinized gingiva amount were reported. Conclusions: fiberotomy is an effective method to prevent relapse of previously rotated teeth and does not cause periodontal alterations. However, it is important to note that the studies’ methodological quality was low.